Comparative studies of neodymium (III)-selective PVC membrane sensors - Gupta, Vinod K. (2009)
Sensors based on two neutral ionophores, N,N-bis((1H-pyrrol-2-yl)methylene)cyclohexane-1,2-diamine (L1) and 3,3-(cyclohexane-1,2-diylbis(azan-1-yl-1-ylidene)bis(methan-1-yl-1-ylidene)bis(5-hydroxymethyl)pyridine-2-ol) (L2) are described for quantification of neodymium (III). Effect of various plasticizers; 2-nitrophenyloctylether (o-NPOE), dibutyl butylphosphonate (DBBP), tri-n-butyl phosphates (TBP), dioctylpthalate (DOP) and chloronapthalen (CN) and anion excluder, sodiumtetraphenylborate (NaTPB) has been studied. The membrane composition of PVC:o-NPOE:ionophore (L1):NaTPB (w/w;mg) of 150:300:5:5 exhibited best performance. The sensor with ionophore (L1) exhibits significantly enhanced selectivity towards neodymium (III) in the concentration range 5.0×10−7 to 1.0×10−2M with a detection limit of 1.0×10−7M and a Nernstian compliance (19.8±0.3mVdecade−1 of activity) within pH range 4.0–8.0. The response time of sensorwas found as 10 s. The influence of the membrane composition and possible interfering ions has also been investigated on the response properties of the electrode. The fast and stable response, good reproducibility and long-term stability of the sensor are observed. The sensor has been found to work satisfactorily in partially non-aqueous media up to 20% (v/v) content of methanol, ethanol or acetonitrile and could be used for a period of 3 months. The selectivity coeffi-cients determined by using fixed interference method (FIM) indicate high selectivity for neodymium. The proposed electrode shows fairly good discrimination of neodymium (III) from other cations. The application of prepared sensor has been demonstrated in the determination of neodymium (III) in spiked water samples.